Metode Analisis Kinerja Sistem Komputer dengan Pendekatan Analisis Kuantitatif - Edy Supriyanto (Dinamik, 2003)
This paper discusses the performance of software, the measurement of software engineering are evaluated by comparative evaluation and analytic evaluation. In this case, the author introduces about quantitative data analysis for measurement of performances software. The tool of measurement of this statistic software e.g. SPSS